PENGUATAN NILAI INTEGRITAS MAHASISWA UNIVERSITAS BANDAR LAMPUNG SEBAGAI UPAYA PREVENTIF DALAM PEMBERANTASAN KORUPSI DI INDONESIA - A.Dinda Alya Ratu Nabila; Alimatul Azizah; Risty Nurhazizah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Corruption is still a serious problem in Indonesia because it has a wide impact on development, public trust, and public welfare. Efforts to eradicate corruption have tended to focus on a repressive approach, so a preventive approach is needed through strengthening the value of integrity, especially among students as the next generation of the nation. This study aims to analyze the role of students in the Prevention of corruption and assess the strategy of strengthening the value of integrity in the university environment by involving the perspective of the Tulang Bawang District Inspectorate. The study used a qualitative approach with a descriptive type, where data were obtained through interviews and literature studies. The results showed that students have an important role as agents of change through anti-corruption education, social movements, and the application of the value of honesty in academic life. In addition, the Inspectorate stressed that the Prevention of corruption must be done through continuous coaching and instilling integrity from an early age. The strategy of strengthening integrity can be done through the integration of anti-corruption education in the curriculum, student organization activities, exemplary lecturers, and collaboration with government agencies